A Technology For Developing Cognitive Flexibility In Primary School Students Using Generative AI (Journal of Pedagogical Inventions and Practices, 2026)
This article describes the main characteristics of the "4K" model, as well as the technology for the formation and development of cognitive flexibility, communication skills and critical thinking in the school education system.